A Gentle (without Chopping) Approach to the Full Kostant-Toda Lattice - Damianou, P.A.; Magri, F. (Symmetry, Integrability and Geometry: Methods and Applications, 2005)
In this paper, we propose a new algorithm for obtaining the rational integrals of the full Kostant-Toda lattice. This new approach is based on a reduction of a bi-Hamiltonian system on gl(n, R). This system was obtained by reducing the space of maps from Zn to GL(n, R) endowed with a structure of a pair of Lie-algebroids.